INDICES DE FRECUENCIA Y VECINDAD ORTOGRAFICA PARA UN CORPUS DE PALABRAS DE CUATRO LETRAS - Alameda, José Ramón; Cuetos, Fernando (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
Lexical frequency and orthographic neighbourhood are two very important variables in experiments on word recognition. In this paper, we present a normative study which includes all four letters words selected from a corpus of over 5 million words. The word frequency, number and relative neighbourhood frequency, acumulative neighbourhood frequency and the neighbourhood number in relation to the changing letter are include in this normative study.